â€œJust give her a bananaâ€: An ethnographic exploration of causes of stunting in Aceh, Indonesia - Nouval Ramadhan; Rosaria Indah; Marisa Marisa (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Thirty-seven percent of children in Aceh suffer from stunting. This number is concerning. Several programs offering supplementary nutrition for children in hot areas have been conducted. However, the percentage is decreasing too slowly. It is unclear why those programs were ineffective. The study aims to explore the cause of stunting in children aged 25-59 months in the Kota Sigli Sub-district, Pidie Regency, Aceh, Indonesia. Qualitative research was conducted on January 2022 using ethnographic tools. Data were collected through participant observation, semi-structured interviews with eight (8) mothers of stunted children, and informal interviews with midwives. Result, the findings show that there are various factors that may influence the incidence of stunting in children: failure to provide exclusive breastfeeding, inappropriate complementary feeding, and problems with hygiene and sanitation that affect childrenâ€™s health. In conclusion, this calls for an integrated approach to engaging the Indonesian government, parents, and communities in overcoming the root of the stunting problem: poverty.Keywords:Â